Analysis of technological possibilities of N‒O‒C‒H system arc plasma in surface engineering processes - Pashchenko, Valeriy (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this study was the substances that could be used to generate arc plasma. Conventional and promising plasma media were analyzed in order to identify the most universal one in terms of a set of properties for efficient energy transfer of material. It is shown that the mean-enthalpy media have a harmonious ratio of temperature and enthalpy and could provide a change in the energy state of the processed material with maximum efficiency. It is established that the most universal set of properties is demonstrated by the medium enthalpy plasma of the N‒O‒C‒H system. The use of mixtures of air with hydrocarbons for its generation makes it possible to reach the average mass temperature of (5...7)·103 K and change the oxidative-reducing potential of the plasma medium over a wide range. Given this, heat treatment is possible with maximum preservation of the original composition of the material. Experimental studies of plasma flows of the N‒O‒C‒H system confirmed the presence of reducing components capable of binding oxygen to air that is sucked into the jet. On rich mixtures, the oxygen content in the jet at a distance of 100 mm does not exceed 5 %. The positive effect of combined energy input into plasma-forming substance on the process of generation and formation of plasma jet has been proven. The use of energy of different physical nature makes it possible to maintain the local energy parameters of the plasma flow during material processing. This is due to the release of additional heat as a result of the interaction of plasma and plasma components with ambient air. The use of plasma of the N‒O‒C‒H system in surface engineering technologies could expand the range of processed materials and reduce the operating costs of the process